Ultrasonography-Guided Thermal Ablation for Cervical Lymph Node Metastasis of Recurrent Papillary Thyroid Carcinoma: Is it Superior to Surgical Resection? - Zhang, Xu; Ni, Tu; Zhang, Wenzhi (Frontiers in Endocrinology, 2022)
Aim: To systematically evaluate the safety and efficacy of ultrasonography-guided percutaneous thermal ablation in the treatment for cervical lymph node metastasis (LNM) of recurrent papillary thyroid carcinoma (PTC). Methods: PubMed, PubMed Central(PMC), EMBASE and Cochrane were examined. The inclusion and exclusion criteria were determined and the relevant data were extracted from Library and other databases for LNM thermal ablation of recurrent PTC. The data were analyzed using Stata15.1, Revman5.3 software, and the standard errors of 95% confidence intervals were estimated using fixed or random effects models. Volume reduction rate (VRR), Serum thyroglobulin (Tg) level before and after thermal ablation, the total complications and major complications incidence were analyzed. Results: A total of 18 literature articles were included, including 10 radioffrequency ablation (RFA), 4 laser ablation (LA), and 4 microwave ablation (MWA). A total of 321 patients had 498 LNM. LNM volume changes before and at the last follow-up of thermal ablation (SMD=1.04，I2=8%，95% CI 0.86-1.21，P＜0.0001). The postoperative lymph node VRR was 88.4% (95% CI 77.8%-97.3%，I2= 34%，P＝0.14). Tg measurements before and after thermal ablation (SMD=1.15，95% CI 0.69-1.60，I2=84%，P＜0.0001). The incidence of total complications was 5.0% (95% CI 3.0%-7.0%，I2=0.0%，P＝0.915), the incidence of major complications was 4.0%(95% CI 2.0%-6.0%，I2=0.0%，P＝0.888). A total of 131 LNM were located in the central region, and the major complication rate was 12.0%(95% CI 6.0%-18.0%，I2=0.0%，P＝0.653). Conclusion: Ultrasonography guided thermal ablation is safe and effective in the treatment for LNM of recurrent PTC. The ablation strategy of central LNM needs to be further explored and improved. It can be used as an alternative to surgery for patients with high surgical risk or who refuse resurgery.